2006
DOI: 10.1210/jc.2006-0913
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β-Cell Function in Human Aging: Response to Nicotinic Acid-Induced Insulin Resistance

Abstract: Human aging is associated with impaired beta-cell sensitivity to glucose and impaired beta-cell compensation to insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 28 publications
3
55
0
3
Order By: Relevance
“…In the report by Gautier et al [20], the participants at increased risk of diabetes had impaired glucose sensitivity in spite of a similar fasting secretory tone. In addition, in a more recent study employing the graded glucose infusion test in young healthy participants [21], the induction of insulin resistance by administration of nicotinic acid produced an increase in fasting insulin secretion without changing the relationship between insulin secretion and glucose concentration.…”
Section: Discussionmentioning
confidence: 96%
“…In the report by Gautier et al [20], the participants at increased risk of diabetes had impaired glucose sensitivity in spite of a similar fasting secretory tone. In addition, in a more recent study employing the graded glucose infusion test in young healthy participants [21], the induction of insulin resistance by administration of nicotinic acid produced an increase in fasting insulin secretion without changing the relationship between insulin secretion and glucose concentration.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, as shown in Fig. 2, the insulin secretion rate in response to glucose was significantly and progressively decreased in older individuals, with the greatest impairment in older individuals with impaired glucose tolerance compared with older individuals with normal glucose tolerance or with younger individuals matched for degree of insulin resistance (9). In fact, a 50% reduction in b-cell secretory capacity has been observed in older men compared with younger men in response to arginine stimulation (29).…”
Section: Effects Of Agingmentioning
confidence: 87%
“…46,[49][50][51][52][53][54][55] Our recent studies have shown that there is a strong lag-correlation between the prevalence of obesity and diabetes in the US population and the increased per capita consumption of niacin, which was attributed primarily to the consumption of fortified grains. 34,35 The toxic effects of niacin may involve a variety of mechanisms, including methyl depletion, changes in NAD-dependent reactions and excessive ROS generation.…”
Section: Arsenicmentioning
confidence: 99%